The Nasalization Processes in Bribri in the Framework of the Optimality Theory - Krohn, Haakon S. (2021)
At the phonological level, the Bribri language does not possess nasal consonants, but it does have a series of nasal vowel phonemes that contrast with the oral vowels. Three phonological nasalization processes affect voiced consonants and unstressed vowels and produce nasal allophones: nasal harmony with regressive spreading, progressive nasalization of syllable codas and nasalization in codas as a result of hypervoicing. These three processes are analyzed in the present paper within the framework of the Optimality Theory. I suggest that two different alignment constraints are the instigators of the nasal harmony and the progressive nasalization, and that the hypervoicing, depending on the case, is a consequence of a constraint that penalizes [b] in codas or of one that penalizes geminated voiced consonants.